Acute Myocardial Infarction Complicating Active Ulcerative Colitis: A Case Report - Eva D. Papadimitraki; Mubarak Ahamed; Nicholas H. Bunce (Case Reports in Cardiology)
Ulcerative colitis (UC) is a chronic inflammatory disease that predominantly affects the gastrointestinal (GI) tract but can involve extraintestinal organs including musculoskeletal system and skin. The most frequent cardiac manifestations of UC are pericarditis and myocarditis. Patients display an increased risk for venous thromboembolic complications and mesenteric ischemia, but the association with ischemic heart disease and myocardial infarction is uncertain. We present the case of a 27-year-old man with anti-PRIII ANCA-positive ulcerative colitis and increased factor VIII activity who presented with an acute myocardial infarction. We discuss possible causative links between these clinical entities and demonstrate the role of cardiac magnetic resonance (CMR) in patients with underlying inflammatory conditions who present with chest pain and evidence of myocardial damage.